A Rare Case of Pulmonary Atresia with Ventricular Septal Defect with a Right Sided Aortic Arch and a Calcified Pulmonary AVM Presenting in an Adult without Cyanosis - Devendra V. Kulkarni; Rahul G. Hegde; Ankit Balani; Anagha R. Joshi (Case Reports in Radiology)
Pulmonary atresia with ventricular septal defect (PA-VSD) with pulmonary arterial supply arising from the aorta representing large MAPCAs associated with a right sided aortic arch is an uncommon anomaly. Most of the patients succumb to severe respiratory compromise or congestive cardiac failure very early. We report the clinical details and imaging findings of a case of PA-VSD with a right sided aortic arch and a calcified pulmonary arteriovenous malformation (AVM) in a 21-year-old postpartum female with no previous episodes of cyanosis who was diagnosed as having a cardiac anomaly on echocardiography when she presented with breathlessness during the 8th month of the pregnancy.